Graphene-based terahertz antenna with enhanced backscatter sensitivity for early breast cancer localization - Al Gburi, Ahmed Jamal Abdullah; Gupta, Anupma; Bansal, Shonak; Kumar, Vipan; Garg, Sonu Bala (Elsevier B.V., 2025)
Terahertz (THz) imaging is emerging as a promising technique for early breast cancer detection due to its high sensitivity to tissue property variations. This paper presents a compact graphene-based patch antenna designed for broadband operation, occupying only 18 µm × 23 µm. The antenna achieves a wide bandwidth of 5.9 THz (3.1–9 THz) and a peak gain of 6.47 dBi without tissue loading, enabled by a full ground plane that ensures unidirectional radiation. To evaluate its performance for cancer detection, numerical breast phantoms with and without tumors were modeled. A significant S11 deviation of up to 16 dB was observed between healthy and cancerous tissue, indicating strong sensitivity to dielectric changes. Additionally, tumor localization was achieved by analyzing the spatial variation of the backscattered signal along the X and Y axes. The results confirm that the proposed antenna can detect minute tumors (∼10 µm radius) and effectively differentiate between malignant and healthy tissues, highlighting its potential for early-stage breast cancer screening.